Tudor catholics : catholic reformation and devotional accountability in Henry's VIII'S England - Lima, Rebeca Mylena Gouveia de (2026)
Tese (doutorado) — Universidade de Brasília, Instituto de Ciências Humanas, Departamento de História, Programa de Pós-Graduação em História, 2026.